Planning of Uwe River PLTMH Jayawijaya Regency Capacity 2 X 750 KW - Toni Toni; Hendri Hendri (CV. Publikasi Indonesia, 2024)
Indonesia has great potential to develop renewable energy, especially through Micro Hydro Power Plants (MHP) that utilize river flow. The Papua region, including Jayawijaya Regency, has significant water resources potential but has not been optimally utilized to meet local energy needs. This study aims to evaluate the technical feasibility of building an MHP in Uwe River, Jayawijaya Regency, with a capacity of 2 x 750 kW as an effort to increase the electrification ratio in Papua Mountains. The research uses a quantitative approach with field survey methods and primary data collection, such as water discharge measurements and interviews with relevant parties. The data were analyzed using the FJ Mock method for water discharge estimation and hydraulic power calculation to assess the technical feasibility of MHP development. The results showed that Uwe River has a potential hydraulic power of 2063.965 kW with a capacity factor of 88%, which is able to support the operation of two turbines with a capacity of 733.76 kW each. The conclusion of this study shows that the construction of an MHP in Sungai Uwe is technically feasible and has great potential to increase the electrification ratio, support local economic development, and reduce dependence on fossil fuels in remote areas. The implication of these results is the importance of investment and policy support in the development of renewable energy projects in Papua to achieve national electrification targets.